Analisis Performa Mekanisme Error Recovery Menggunakan Automatic Repeat Request (ARQ) dan Forward Error Correction (FEC) pada Multi Receiver File Transfer - Kusnul Aeni; Mahendra Data; Adhitya Bhawiyuga (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
File transmission from one to multi receiver has higher probability in packet loss compare with one to one transmission. Error recovery mechanism is needed to overcome packet loss. Error recovery mechanism that common use is ARQ (Automatic Repeat Request) and FEC (Forward Error Correction). This research aim is to compare the error recovery performance of ARQ and FEC mechanism. Example of ARQ application based reliable multicast transfer is UFTP, and the example of FEC application mechanism based on reliable multicast transfer is UDPCast. In this research, testing process was done with text files transmission using WANem (Wide Area Network Emulator) as a network emulator. There are 5 file redundant categories (in percent) added in FEC mechanism that will affect the file transmission. In this research, there are 30 scenarios for testing based on packet loss category and file size to be sent. All file used for testing has the size in the range of 20 MB to 100 MB. The test result indicate that in a good network condition, in general the use of error recovery mechanism, ARQ has better performance than FEC mechanism. Meanwhile, in a poor condition (with 25% packet loss), the used of FEC mechanism is better choice.